PENGEMBANGAN SUNGAI TEMATIK DI DESA PENDEM KECAMATAN JUNREJO KOTA BATU - Yeyen Pratika; Ardik Praharjo (Universitas Muhammadiyah Malang, 2021)
The community service program purposes to develop a clean and beneficial river for the community in order to raise the awareness of the importance of family medicinal plants. The problem in this area was the lacking of public awareness to protect the environment, especially the river. In addition, the community also needs an access to adequate medical treatment through the advantage of family medicinal plants. The location of this community service is very appropriate because people in this area demand a better change in their environment, especially the existing river in their area, and can create from it. The method used in this service is tutorial, discussion, demonstration and assistance. The result of this program indicates that the river management in this area can be developed well and the family medicinal plants can be used optimally. The community can also find out about the use of family medicinal plants for their family.